Cross Sector Collaboration in Integrasi Sustainable Development Goals (SDGs) at Village Development Planning - Zulkarnain Hamson; Muhammad Nasir Mahmud; Nani Harlinda Nurdin (Pinisi Business Administration Review, 2022)
Village Sustainable Development Goals (SDGs) are sustainable development goals that are integrated into the priority program for the use of village funds in 2021. Village SDGs are expected to be a reference for village development in 2020-2024. However, with all the limitations that exist in the village, both human resources and institutions, there are still obstacles in its application. The purpose of this study is to examine the collaboration model as a policy strategy in preparing SDGs-based village development plans and programs. The method used in this study uses qualitative methods. Data collection was carried out through observation and interviews as well as existing documentation. The process of data analysis through reduction and presentation of data and conclusions. The results showed that the cross-sectoral collaboration that involved the power of Penta Helix had not been implemented in order to significantly contribute to village development and cross-sector collaboration was not designed in rural areas. The upper level government, namely the district, also does not have a collaborative mechanism to integrate SDGs with development plans down to the village level. Cross-sectoral collaboration mechanisms in the process of integrating Village SDGs into village development planning, Bontolanra Village, Galesong Utara District, Takalar Regency.